MOTIVATIONAL LEVELS OF HEALTHCARE PROFESSIONALS IN INDIA DURING COVID-19 OUTBREAK - et. al., Ellora Gogai (International Journal of Modern Agriculture, 2021)
The novel COVID-19 pandemic has challenged the entire human race. While, countries are under lockdown and people in social isolation, our healthcare workers are still out there every day, fighting this war by jeopardizing their lives. They are continuously supporting and treating patients and also dealing with overwhelming workload, emotional stressors, moral dilemmas, chances of getting exposed and so on. As such, for uninterrupted and effective functioning of the healthcare facilities under the pressure of such a crisis, it is of utmost importance to maintain good physical and mental health of the professionals. The first step towards that, is identifying the factors which increases and decreases the willingness of the professionals to work. There have been studies in the past which explained the factors which affects employee commitment and employee motivation towards work in the healthcare sector. And how workers in healthcare sector operates during a crisis situation, but so far, there have been no cross-sectional studies conducted on employee commitment of healthcare professionals in India at real-time during COVID-19 pandemic. This study aims at identifying few of the important factors behind motivation level of healthcare professionals towards work at the time of COVID-19 and the mediating role of HRM towards addressing some of the concerns of the workforce. The study is focused on a group of healthcare professionals in Assam who are working in hospitals, treating COVID-19 infected patients. The focus group consists of 123 respondents. With the help of binomial logistic regression modelling in SPSS, we were able to identity how much the independent variables impacted the dependent variable, which is motivation level of the workforce. Results show, transparency in communication of leadership greatly helps in motivating the workforce with an odds ratio(OR) of 6.773. Also, the respondents who received training regarding the crisis has an OR of 2.007, which means, they are two times more motivated to work than respondents who did not receive training. Other factors such as; good leadership who lead by examples, support from supervisors and co-workers, gestures of appreciation to name a few. On the contrary, the major reasons for low motivation levels were inhibitions related to risk for infection, mental exhaustion, lack of knowledge about protection, uncertainty about cure, and feeling of isolation